The burden and epidemiology of polyparasitism among rural communities in Kano State, Nigeria. (25th March 2019) - Dawaki, Salwa; Al-Mekhlafi, Hesham M; Ithoi, Init
Abstract: Background: Parasitic infections constitute a major public health problem worldwide, particularly among underprivileged communities in developing countries including Nigeria. The present study aimed to determine the epidemiology of polyparasitism (multiple parasitic infections) among rural communities in Kano State, North Central Nigeria. Methods: A total of 551 individuals were screened for the presence of intestinal, urogenital and blood parasites by using different diagnostic techniques. Demographic, socioeconomic, household and behavioural characteristics were collected using a pre-tested questionnaire. Results: Overall, 84.0% (463/551) of the participants were found to be infected with at least one parasite species, with 51.2% (282/551) of them having polyparasitism. The most prevalent parasites were Plasmodium falciparum (60.6%) followed by Blastocystis sp. (29.2%) and hookworm (15.4%). No significant association was found between malaria and helminth infections (p>0.05). Univariate and multivariate analyses showed that the presence of other family members who had intestinal polyparasitism (adjusted odds ratio [AOR]=4.12; 95% CI=2.72, 6.24), walking barefoot outside (AOR=1.70; 95% CI=1.09, 2.63) and being male (AOR=1.74; 95% CI=1.14, 2.66) were the significant risk factors of intestinal polyparasitism among the population studied. Conclusion: Polyparasitism is highly prevalent among rural communities in Kano State. Therefore, effective, sustainable and integrated control measures should be identified and implemented to significantly reduce the burden and consequences of these infections in rural Nigeria.